Circular RNAs in diabetes and its complications: Current knowledge and future prospects - Yin, Wenfeng; Zhang, Ziwei; Xiao, Zilin; Li, Xia; Luo, Shuoming; Zhou, Zhiguang (Frontiers in Genetics, 2022)
A novel class of non-coding RNA transcripts called circular RNAs (circRNAs) have been the subject of significant recent study. Accumulating evidence points that circRNAs play an important role in the cellular processes, inflammatory expression and immune responses through sponging miRNA, binding or translating in proteins. Studies have found that circRNAs are involved in the physiologic and pathologic processes of diabetes. There has been an increased focus on the relevance of between abnormal circRNA expression and the development and progression of various types of diabetes and diabetes-related diseases. These circRNAs not only serve as promising diagnostic and prognostic molecular biomarkers, but also have important biological roles in islet cells, diabetes, and its complications. In addition, many circRNA signaling pathways have also been found to regulate the occurrence and development of diabetes. Here we comprehensively review and discuss recent advances in our understanding of the physiologic function and regulatory mechanisms of circRNAs on pancreatic islet cells, different subtypes in diabetes, and diabetic complications.